If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6n + 2 = -106 Reorder the terms: 2 + 6n = -106 Solving 2 + 6n = -106 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 6n = -106 + -2 Combine like terms: 2 + -2 = 0 0 + 6n = -106 + -2 6n = -106 + -2 Combine like terms: -106 + -2 = -108 6n = -108 Divide each side by '6'. n = -18 Simplifying n = -18
| 7(w-6)+1=-13 | | 12onethird=13(7x+15) | | -22=2-6n | | 3=-16t^2-15t+30 | | x-3=1.5 | | 3a-3b=-15 | | 6a^3+15a=equation | | x^2-5ax+6a^2=0 | | 9w+40=-2(w+2) | | 90=-16t^2+155 | | x+8=2.5 | | -2+3(4p-1)=-3+40 | | 90=-16t^2-155 | | 36z+6-132= | | n+21/2=7 | | 0=-16t^2+30t+15 | | (6)(5)(-2)= | | a+18=17a | | 7+n=-4 | | 12x^2-44x+144=0 | | 4.6z=17.02 | | 3=-16t^2+15t+30 | | k+14.2=9.8 | | 3+1/3 | | 5.7b=29.64 | | 24=d(3.14) | | 150=-16t^2+60t+5 | | 89-x=29 | | 3.5=m-2.2 | | y=1/2x^2 | | 24=2x(3.14) | | 16t^2-60t+45=0 |